Pre-Primary Education in Mongolia : Access, Quality of Service Delivery, and Child Development Outcomes - World Bank (World Bank, Washington, DC, 2017)
Sustaining in recent years expenditure on early childhood education (ECE) at over a fifth of its education budget, Mongolia is a relatively high spender on pre-primary education. This report examines structural and process aspects of quality in Mongolian kindergartens, along with early development outcomes among children enrolled in these kindergartens, to assess the effectiveness and equity of the country's public investments in ECE. The analysis shows that while the last decade saw tremendous progress in improving access to preschool overall, the most disadvantaged and vulnerable are still excluded from the system. Further, an assessment of child development outcomes shows that even after significant exposure to formal preschool services in the public sector, socioeconomic gaps in outcomes remain large. At the same time, potential areas where relatively low-cost investments could reap significant gains remain unexploited. Key among these is use of home- or community-based ECE interventions that could improve school preparedness among children in rural areas not enrolled in preschools. Another is the potential for an expanded role for the private sector in urban areas.